Fixed-term Employment and Fertility: Theory and Evidence from German Micro Data - Wolfgang Auer; Natalia Danzer; Helmut Rainer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In Germany, it has become conventional wisdom that the economic uncertainty associated fixed-term employment contracts prevents young couples from realizing their desire to have children. From a research perspective, it is however far from clear whether fixed-term contracts are the obstacle to family formation that the public a priori expect them to be. In this paper, we first develop a simple dynamic bargaining model that allows us to ask theoretically: under what conditions will couples choose to have children early on in life, postpone it to later in life, or decide to remain childless? And: to what extent does the economic uncertainty associated with holding fixed-term employment contract affect these choices? We obtain two theoretical predictions. On the one hand, job uncertainty at the beginning of women's employment careers causes couples to postpone parenthood. On the other hand, job uncertainty in women's mid-career lives causes couples to enter parenthood instead of remaining voluntarily childless. We bring these theoretical predictions to data from the German Socio-Economimc Panel (SOEP). Ordinary least squares and fixed-effects estimations show that, at the beginning of women's employment careers, holding a fixed-term employment contract and the probability of entering parenthood are negatively correlated. When considering women in their mid-career lives, holding a fixed-term contract has a positive impact on the probability of entering parenthood.
Keywords: D13; J13; J22; 330